Analysis of the Needs for Christian Religion for Elderly Age at the Tresna Werdha Sinta Rangkang Social Home - Teresa Tabita Monika; Matius Timan Herdi Ginting; Sarmauli Sarmauli (Journal of Midwifery History and Philosophy, 2026)
Background. Old age is often considered a burden for productive people. This is motivated by the aging process, which includes physical decline and psychological and social problems. Seeing this, the church must take a role in discipling its people and not ignore the needs experienced by old age. Purpose. This is intended so that the church can take part in the welfare of the elderly by paying attention to every aspect of their growth and making it contextual with the Christian religious guidance provided. Methods. This study uses qualitative methods with descriptive types and data collection techniques, namely in-depth interviews, observation, and documentation. Results. The research results obtained from defining psychological and psychological-sociological needs based on B.S. Sidjaga, Ed.D is that the elderly tend to feel sad, easily suspicious, defend themselves against experiences, egocentrism, stress due to family, and tend to have irritable emotions. Furthermore, in the psychological-sociological phase, which tends to be in the phase of despair in line with Erik Erikson's theory of feeling worried, anxious, and afraid, This feeling is felt by almost all the elderly at the Tresna Werda Sinta Rangkang Social Institution, due to their background age before entering the orphanage and their decline. Conclusion. The elderly require coaching in psychological and psychological-sociological fields, as they often experience the indicators of integrity vs. despair, as per Erik Erikson's developmental theory. However, Christian religious formation at PSTW Sinta Rangkang has not prioritized these psychological conditions, leading to general teaching materials and monotonous coaching. To address this, Christian Religious Development should collaborate with churches, communities, and other Christian institutions, provide teaching materials that address the needs and struggles of the elderly, and create a written curriculum that outlines objectives, materials, methods, and evaluation of coaching activities